EVALUASI PROGRAM PENCEGAHAN PENULARAN HIV DARI IBU KE ANAK DI PUSKESMAS BOGOR TIMUR KECAMATAN BOGOR TIMUR KOTA BOGOR - Ziyan Capella Amalia; Budi Puspo Priyadi; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2023)
Currently, the spread of HIV-AIDS has reached housewives and infants who aren’t part of the key population. More than 90% of cases of children infected with HIV are transmitted through HIV mothers. During breastfeeding, the risk of HIV transmission to children is 20%. The government's efforts to deal with the transmission of HIV from mother to child are through the procedure of feeding infants or children in the Prevention of Mother to Child Transmission program (PMTCT). East Bogor sub-district is one of the areas that has a high number of HIV-AIDS cases, including the number of HIV cases among housewives. This research aims to analyze the procedure for feeding infants or children in the PMTCT program at the East Bogor Public Health Center, East Bogor SubDistrict, Bogor City. This research used a qualitative descriptive method with data collection techniques used interviews, observation, and documentation. It came out with the result that these implementing officers at the East Bogor Public Health Center gave directions to mothers with HIV to provide food to their babies in accordance with Minister of Health Regulation Number 51 of 2013 concerning Prevention of HIV Transmission from Mother to Child Guidelines in the form of formula milk without mixed feeding. Then, there are several aspects that hinder the implementation of the procedure of feeding infants or children at the East Bogor Public Health Center, namely: not providing CIE materials or brochures that may be taken home, midwives are less involved in the program, low knowledge regarding HIV-AIDS, a lack of support from family members, and there’s still stigma and discrimination experienced by mothers with HIV, especially in the neighborhood. Thus, it can be concluded that the procedure for feeding infants or children at the East Bogor Public Health Center is still not optimal. Recommendations that can be given from this research are: the need for socialization to abolish stigma and discrimination; the provision of CIE materials or brochures that may be taken home; further training for midwives to participate in the program; active involvement of the MCH clinic is required; and providing detailed education to married PWHA about HIV transmission to infants.